(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Present paper is a study on the positive and negative traits of the two leading characters, Raju and Rosy in R.K. Narayan’s ‘The Guide’ which can be termed as a story ahead of time. It has characters with a modern attitude with conventional background. They both represent the traditional and modern outlook of the society and go through a gradual but balanced change as a consequence of small events that happen in their lives as in the case of any ordinary man. Both of them have got their shortcomings and at the same time strong values. Though they happened to yield or succumb under the pressure of circumstances, they do hold innate good qualities. This research examines both the positive and negative traits of Raju and Rosie with more emphasis on the merits.